Cerium-doped titanium dioxide-carbon fiber composite material and preparation method thereof

The preparation of cerium-doped titanium dioxide-carbon fiber composite materials solves the problem of existing catalytic materials being deactivated at high temperatures and unable to achieve fire prevention and purification functions, achieving efficient degradation of VOCs and improving the fire prevention performance and stability of tunnel coatings.

CN119327442AInactive Publication Date: 2025-01-21INST OF EARTH ENVIRONMENT CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411879878.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing catalytic materials are inefficient in purifying volatile organic compounds (VOCs), and are inactivated or released toxic by-products in high temperature environments, which cannot achieve fire protection and purification functions at the same time, affecting the air quality in the tunnel and the health and safety of passers-by.

Method used

The cerium-doped titanium dioxide-carbon fiber composite material is made by immersing the activated carbon fiber in titanium dioxide sol and cerium nitrate solution, ultrasonic treatment and roasting to achieve effective doping of cerium ions and stable loading of titanium dioxide, thereby improving the photocatalytic activity of the material. and high temperature stability.

Benefits of technology

This material has a degradation rate of VOCs of 74% to 85% under ultraviolet light irradiation in the range of 100~600℃. It also has good fire resistance and structural stability, significantly improves the air quality in the tunnel and enhances the functionality and functionality of the coating. Security.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327442A_ABST
    Figure CN119327442A_ABST
Patent Text Reader

Abstract

The invention discloses a cerium-doped titanium dioxide-carbon fiber composite material and a preparation method thereof.In the preparation process of the cerium-doped titanium dioxide-carbon fiber composite material, activated carbon fibers are immersed in titanium dioxide sol, after ultrasonic treatment and drying, roasting is conducted, and the activated carbon fibers loaded with titanium dioxide are prepared; the activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution, ultrasonic treatment is performed, roasting treatment is performed after drying, and the cerium-doped titanium dioxide-carbon fiber composite material is prepared. The cerium-doped titanium dioxide-carbon fiber composite material prepared in the invention can maintain structural integrity and performance stability in a high-temperature environment, has excellent photocatalytic activity, can efficiently degrade volatile organic compounds (VOCs) and significantly improve air quality, and effectively improves the functionality of a coating when being used as a tunnel coating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of development of functional fire-retardant coatings for tunnels and relates to a cerium-doped titanium dioxide-carbon fiber composite material and a preparation method thereof. Background Art

[0002] With the acceleration of industrialization and urbanization, air pollution is becoming increasingly serious, especially the emission of volatile organic compounds (VOCs), which poses a great threat to the environment and human health. Motor vehicle emissions are one of the main sources of atmospheric VOCs. Under certain conditions, they can also react with other pollutants to generate ozone and fine particulate matter, aggravating air pollution and endangering human health. Highway tunnels, as key infrastructure for urban transportation, often accumulate a large amount of pollutants emitted by automobile exhaust, forming a semi-closed environment with poor air circulation, threatening the health and safety of passers-by. In addition, if a fire occurs inside the tunnel, the existing coatings may release toxic gases at high temperatures, further aggravating the consequences of the disaster. Commonly used highway tunnel coatings cannot purify gaseous pollutants in the air during use, thus affecting the safety and environmental protection of the coatings during overall use. Therefore, it is particularly important to develop a nano-coating that can not only efficiently purify volatile organic compounds but also has fire-proof function.

[0003] Existing catalytic materials have multiple problems in purifying volatile organic compounds (VOCs), which restrict their effectiveness and safety in practical applications. First, the photocatalytic efficiency of many traditional catalytic materials is low, resulting in insufficient ability to degrade VOCs under light conditions, which cannot meet the increasingly severe air purification needs. Secondly, these materials will lose their activity or release toxic byproducts in high temperature environments, posing potential health risks to the human body. Especially in enclosed spaces such as highway tunnels, coatings may release harmful gases in the event of a fire, further exacerbating the consequences of the disaster. In addition, many existing coatings lack comprehensive functions and cannot achieve fire protection and purification functions at the same time, resulting in the inability to effectively protect the health and safety of passers-by in specific application scenarios. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a cerium-doped titanium dioxide-carbon fiber composite material and a preparation method thereof, thereby solving the technical problem in the prior art that the photocatalytic material is deactivated at high temperature and cannot degrade pollutants in special scenarios.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material comprises the following steps: S1: immersing activated carbon fiber in titanium dioxide sol, ultrasonically treating, drying and then calcining to obtain activated carbon fiber loaded with titanium dioxide; S2: immersing the activated carbon fiber loaded with titanium dioxide in a cerium nitrate solution, ultrasonically treating it, drying it, and then calcining it to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0006] Preferably, the titanium dioxide sol is prepared by 18 to 21 parts of low carbon alcohol, 18 to 20 parts of titanium-containing compound, 1.5 to 2.5 parts of inhibitor, and 3 to 5 parts of an aqueous solution with a pH of 6.5 to 7.5, in parts by mass; The low-carbon alcohol is at least one of methanol, ethanol, propanol and butanol; The titanium-containing compound is at least one of titanium dioxide, sodium metatitanate and titanium tetrachloride; The inhibitor is at least one of maleic anhydride, dibutyl phthalate and azelaic acid monoester.

[0007] Preferably, a pore-forming agent is further added during the preparation of the titanium dioxide sol; the pore-forming agent is at least one of glucose, starch, cellulose, hexadecyltrimethylammonium bromide and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0008] Preferably, in step S1, the activated carbon fiber is pretreated before being immersed in the titanium dioxide sol; the pretreatment is specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 2~5mm; grinding the cut activated carbon fiber to a particle size of 200~300 mesh; placing the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution in turn and soaking them for 25~35min respectively, after washing, drying them at 110~130°C, thereby completing the pretreatment process of the activated carbon fiber.

[0009] Preferably, in step S1, the mass ratio of the activated carbon fiber to the titanium dioxide sol is 1:(2-3); the frequency of ultrasonic treatment is 40-55 kHz, the time is 70-80 min, and the temperature is 55-65°C.

[0010] Preferably, in step S1, during the calcination process, the temperature is 300-500° C., the time is 2-4 hours, and the calcination atmosphere is nitrogen or helium.

[0011] Preferably, in step S2, the mass ratio of the activated carbon fiber loaded with titanium dioxide to cerium nitrate is 1:(0.5-2); the ultrasonic treatment time is 20-60 min, and the temperature is 20-50°C.

[0012] Preferably, during the calcination process of step S2, the temperature is 200-220°C, the time is 2-4 hours, and the calcination atmosphere is nitrogen or helium.

[0013] A cerium-doped titanium dioxide-carbon fiber composite material is prepared by the above method; the cerium-doped titanium dioxide-carbon fiber composite material has a degradation rate of 74% to 85% for VOCs under ultraviolet light irradiation within 100 to 600°C.

[0014] A nano fireproof tunnel coating with a purification function comprises, by weight, 200-240 parts of the above-mentioned cerium-doped titanium dioxide-carbon fiber composite material, 100-140 parts of bactericidal and insect repellent composite powder, 200-250 parts of inorganic alkali metal silicate, 150-250 parts of modified silica sol, 100-150 parts of kaolin, 60-100 parts of expanded vermiculite, 10-20 parts of vitrified microspheres, 20-50 parts of glass microspheres, 80-120 parts of aluminum hydroxide, 10-20 parts of ammonium polyphosphate, 12-15 parts of melamine, 100-200 parts of nitrogen-vanadium co-doped nano titanium dioxide, 50-80 parts of organic silicon modifier, 70-90 parts of composite auxiliary agent and 150-180 parts of flame retardant.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of a cerium-doped titanium dioxide-carbon fiber composite material. First, during the preparation process, activated carbon fibers are immersed in titanium dioxide sol, and through ultrasonic treatment and calcination, titanium dioxide is uniformly and firmly loaded on the fiber surface, which not only enhances the overall structural strength of the material, but also improves its thermal stability; subsequently, the activated carbon fibers loaded with titanium dioxide are further immersed in a cerium nitrate solution, and through ultrasonic treatment and calcination again, effective doping of cerium ions is achieved, and the introduction of cerium ions not only optimizes the crystal structure of titanium dioxide, but also forms a more stable chemical bond, wherein, after cerium is doped, a stable Ce-O-Ti can be formed between cerium and titanium, and at the same time, cerium ions can also form Ce-OC with the surface of carbon fiber during the calcination process, which effectively improves the overall structural stability of the material and the thermal stability of the composite material, and the doping of cerium may also enhance the interface bonding force between titanium dioxide and carbon fiber, so that the composite material can still maintain good mechanical properties at high temperatures. Therefore, the cerium-doped titanium dioxide-carbon fiber composite material prepared in the present invention can maintain structural integrity and performance stability under high temperature environment, and at the same time has excellent photocatalytic activity, can efficiently degrade volatile organic compounds (VOCs), and significantly improve air quality. When it is used for tunnel coating materials, it effectively improves the functionality of the coating, and also provides an effective solution for the safety and environmental friendliness of special environments such as tunnels, thereby promoting the sustainable development of public facilities.

[0016] Further, the titanium dioxide sol is prepared by 18 to 21 parts of low-carbon alcohol, 18 to 20 parts of titanium-containing compounds, 1.5 to 2.5 parts of inhibitors, and 3 to 5 parts of an aqueous solution with a pH of 6.5 to 7.5, according to the weight percentage; the low-carbon alcohol is at least one of methanol, ethanol, propanol and butanol; the titanium-containing compound is at least one of titanium dioxide, sodium metatitanate and titanium tetrachloride; the inhibitor is at least one of maleic anhydride, dibutyl phthalate and azelaic acid monoester. The method can ensure that the composition of the sol is uniform and stable by accurately controlling the weight percentages of the low-carbon alcohol, the titanium-containing compound and the inhibitor. , which is beneficial to improving the quality of subsequent composite materials; the addition of inhibitors can control the reaction rate of the gel polymerization process, prevent excessive polymerization, help form a uniform nanostructure, and avoid the formation of uneven particle size or agglomeration in the material; secondly, the use of low-carbon alcohols as solvents not only helps to reduce the viscosity of the sol and improve its impregnation effect on the activated carbon fiber, but also makes it easier to volatilize during the calcination process, avoiding adverse effects on the performance of the composite materials; in addition, by adjusting the pH value of the sol within the range of 6.5~7.5, the stability and dispersibility of the sol can be further optimized, providing better conditions for the subsequent doping of cerium ions.

[0017] Furthermore, a pore-forming agent is added during the preparation of the titanium dioxide sol; the pore-forming agent is at least one of glucose, starch, cellulose, hexadecyltrimethylammonium bromide and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer. The addition of the pore-forming agent can form a tiny pore structure in the sol, and these pores will become micropores or mesopores in the composite material during the subsequent calcination process, thereby increasing the specific surface area and porosity of the material. The increase in specific surface area is conducive to improving the material's gas adsorption capacity and catalytic activity, while the increase in porosity helps to improve the material's permeability and mass transfer efficiency. In addition, the use of a pore-forming agent can also adjust the viscosity and fluidity of the sol, making it easier to impregnate into activated carbon fibers and form a uniform and dense titanium dioxide coating on the fiber surface.

[0018] Furthermore, in step S1, the activated carbon fiber is pretreated before being immersed in the titanium dioxide sol; the pretreatment is specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 2-5 mm; grinding the cut activated carbon fiber to a particle size of 200-300 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 25-35 min respectively, washing, and drying at 110-130°C, that is, completing the pretreatment process of the activated carbon fiber. By cutting, the cross-sectional diameter of the activated carbon fiber is controlled within the range of 2-5 mm, which is not only conducive to the subsequent grinding process, but also conducive to the subsequent grinding process. Uniformity can also ensure better impregnation effect of fiber in sol; secondly, grinding to a particle size of 200-300 mesh makes the surface of activated carbon fiber more delicate, which is conducive to the penetration and adhesion of sol, thereby increasing the loading amount and uniformity of titanium dioxide on the fiber surface; in addition, the ground product is sequentially immersed in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution to effectively remove impurities and oil stains on the fiber surface, while adjusting the acidity and alkalinity of the fiber surface and the distribution of functional groups to improve its binding force with titanium dioxide sol; finally, drying at 110-130°C can completely remove moisture and solvent residues in the fiber, laying a good foundation for subsequent sol impregnation and roasting processes.

[0019] Furthermore, in step S1, the mass ratio of the activated carbon fiber to the titanium dioxide sol is 1:(2~3); the frequency of the ultrasonic treatment is 40~55kHz, the time is 70~80min, and the temperature is 55~65°C. First, the mass ratio of the activated carbon fiber to the titanium dioxide sol is set to 1:(2~3), which can ensure that the sol is fully impregnated into the interior and surface of the fiber to form a uniform and dense titanium dioxide coating, while avoiding excessive sol resulting in waste or affecting subsequent treatment; secondly, the frequency of the ultrasonic treatment is selected in the range of 40~55kHz, which can effectively promote the penetration and dispersion of the sol in the fiber and improve the loading efficiency. The treatment time is set to 70~80min, which can ensure that the sol fully impregnates the fiber and achieves a good loading effect. The treatment temperature is controlled at 55~65°C, which is conducive to maintaining the stability and fluidity of the sol, avoiding excessive temperature causing premature gelation of the sol or excessively low temperature affecting the impregnation effect. Furthermore, in step S1, during the calcination process, the temperature is 300-500°C, the time is 2-4 hours, and the calcination atmosphere is nitrogen or helium. First, the appropriate calcination temperature is conducive to the pyrolysis and crystallization of the titanium dioxide sol on the activated carbon fiber, forming a stable and firm titanium dioxide coating. Too low a temperature leads to incomplete pyrolysis of the sol, affecting the loading effect; while too high a temperature causes damage to the fiber structure or unnecessary chemical reactions; secondly, the reasonable control of the calcination time ensures that the sol is fully pyrolyzed and converted into the desired titanium dioxide form, while avoiding the negative effects that may be caused by long-term high-temperature treatment; finally, choosing nitrogen or helium as the calcination atmosphere can effectively prevent oxygen from oxidizing the activated carbon fiber and protect the integrity of the fiber structure. At the same time, these inert gases also help to discharge volatile substances generated during the pyrolysis of the sol and promote the crystallization and purification of titanium dioxide.

[0020] Furthermore, in step S2, the mass ratio of the activated carbon fiber loaded with titanium dioxide to cerium nitrate is 1:(0.5~2); the time of ultrasonic treatment is 20~60min, and the temperature is 20~50℃. First, the mass ratio of the activated carbon fiber loaded with titanium dioxide to cerium nitrate is set to 1:(0.5~2). This ratio range ensures that cerium ions can be uniformly and effectively doped into the titanium dioxide coating, and neither the expected doping effect can be achieved due to too low cerium content, nor agglomeration or phase separation can be caused due to too high cerium content. Secondly, the time of ultrasonic treatment is controlled within 20~60 min, which can fully promote the penetration and diffusion of cerium nitrate solution on the fiber surface and realize uniform distribution of cerium ions, and will not destroy the fiber structure or cause unnecessary energy consumption due to too long treatment time. In addition, the temperature of ultrasonic treatment is set within the range of 20~50℃, which is conducive to maintaining the fluidity and stability of the solution, avoiding chemical reactions or phase changes caused by high temperature, and ensuring the safety and operability of the treatment process.

[0021] Furthermore, during the calcination process of step S2, the temperature is 200-220°C, the time is 2-4 hours, and the calcination atmosphere is nitrogen or helium. First, the appropriate calcination temperature ensures the effective decomposition of cerium nitrate and the uniform doping of cerium ions into the titanium dioxide coating, while avoiding the destruction of the fiber structure or unnecessary chemical reactions that may be caused by excessively high temperatures; secondly, the reasonable control of the calcination time allows the cerium ions to have sufficient time to diffuse in the titanium dioxide lattice and reach a stable state, while ensuring the completeness and efficiency of the doping process; in addition, selecting nitrogen or helium as the calcination atmosphere effectively prevents the oxidation of oxygen on the composite material and protects the integrity of the fiber and the titanium dioxide coating. At the same time, these inert gases also help to discharge volatile substances generated during the calcination process, thereby promoting the purification and densification of the composite material.

[0022] In addition, the present invention also discloses a nano fireproof tunnel coating with a purification function, which comprises, by weight, 200-240 parts of the cerium-doped titanium dioxide-carbon fiber composite material described in claim 9, 100-140 parts of bactericidal and insect-repellent composite powder, 200-250 parts of inorganic alkali metal silicate, 150-250 parts of modified silica sol, 100-150 parts of kaolin, 60-100 parts of expanded vermiculite, 10-20 parts of vitrified microspheres, 20-50 parts of glass microspheres, 80-120 parts of aluminum hydroxide, 10-20 parts of ammonium polyphosphate, 12-15 parts of melamine, 100-200 parts of nitrogen-vanadium co-doped nano titanium dioxide, 50-80 parts of organic silicon modifier and 70-90 parts of composite auxiliary agent. The coating contains 200-240 parts of cerium-doped titanium dioxide-carbon fiber composite material. This composite material not only has excellent catalytic properties, can decompose harmful gases and purify the air, but also its carbon fiber base gives the coating good mechanical properties and thermal stability, which helps to improve the overall durability and fire resistance of the coating. The bactericidal and insect repellent composite powder in the coating provides additional hygienic protection for the tunnel, effectively inhibits bacterial growth and pest infestation, and improves the hygienic level of the tunnel environment. The application of inorganic components such as inorganic alkali metal silicates, modified silica sols, and kaolin significantly enhances the adhesion and water resistance of the coating, allowing the coating to remain stable for a long time in a humid environment such as a tunnel. The addition of lightweight fillers such as expanded vermiculite, vitrified microspheres, and glass microspheres not only reduces the density of the coating and improves its thermal insulation performance, but also helps to form an insulation layer when a fire occurs, delaying the spread of the fire. The introduction of flame retardant ingredients such as aluminum hydroxide, ammonium polyphosphate, and melamine significantly improves the fire resistance level of the coating, which can effectively prevent the spread of fire in a fire and protect the safety of the tunnel structure. In particular, the addition of nitrogen-vanadium co-doped nano-titanium dioxide further enhances the purification function of the coating, and synergizes with the cerium-doped titanium dioxide-carbon fiber composite material to jointly improve the air quality in the tunnel. The addition of silicone modifiers improves the flexibility and weather resistance of the coating, allowing the coating to better adapt to the complex and changeable environmental conditions of the tunnel. Finally, the addition of composite additives not only optimizes the construction performance of the coating, but also improves the overall performance of the coating. In summary, the fire-resistant tunnel coating of the present invention performs well in terms of fire resistance, purification function, mechanical properties, weather resistance and construction performance, providing a strong guarantee for the safe operation of the tunnel and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 It is a schematic diagram of a process for preparing a cerium-doped titanium dioxide-carbon fiber composite material in the present invention; Figure 2 This is a SEM image of a cerium-doped titanium dioxide-carbon fiber composite material prepared in Example 1 of the present invention; Figure 3 The VOC degradation performance test comparison results of the nano fireproof tunnel coating with purification function prepared in Example 1 of the present invention and the coatings prepared in Comparative Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0030] like Figure 1 As shown, the present invention provides a method for preparing a cerium-doped titanium dioxide-carbon fiber composite material, comprising the following steps: S1: pretreating the activated carbon fiber, specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 2-5 mm; grinding the cut activated carbon fiber to a particle size of 200-300 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 25-35 minutes respectively, washing, and drying at 110-130°C, thereby completing the pretreatment process of the activated carbon fiber.

[0031] S2: immersing the activated carbon fiber in titanium dioxide sol at a mass ratio of 1:(2~3), ultrasonically treating it at a frequency of 40~55kHz and a temperature of 55~65℃ for 70~80min, drying it, and calcining it at 300~500℃ in a nitrogen or helium atmosphere for 2~4h to obtain activated carbon fiber loaded with titanium dioxide; The titanium dioxide sol is prepared by 18 to 21 parts of low carbon alcohol, 18 to 20 parts of titanium-containing compound, 1.5 to 2.5 parts of inhibitor, and 3 to 5 parts of aqueous solution with a pH of 6.5 to 7.5, in parts by mass; The low-carbon alcohol is at least one of methanol, ethanol, propanol and butanol; the titanium-containing compound is at least one of titanium dioxide, sodium metatitanate and titanium tetrachloride; the inhibitor is at least one of maleic anhydride, dibutyl phthalate and azelaic acid monoester. A pore-forming agent is also added during the preparation of the titanium dioxide sol; the pore-forming agent is at least one of glucose, starch, cellulose, hexadecyltrimethylammonium bromide and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0032] S3: The activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution at a mass ratio of 1:(0.5~2), ultrasonically treated at a temperature of 20~50°C for 20~60min, dried, and calcined at a temperature of 200~220°C in a nitrogen or helium atmosphere for 2~4h to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0033] At the same time, the present invention also discloses a cerium-doped titanium dioxide-carbon fiber composite material prepared by the above method. The cerium-doped titanium dioxide-carbon fiber composite material has a degradation rate of 74% to 85% for VOCs under ultraviolet light irradiation within 100 to 600°C.

[0034] In the present invention, cerium element is doped into nano titanium dioxide to prolong the life of photogenerated electron-hole pairs, improve the quantum effect of nano titanium dioxide, and further achieve the purpose of improving the photocatalytic activity of nano titanium dioxide; the nano fireproof tunnel coating obtained by the method has high degradation efficiency for volatile organic pollutants, so in the subsequent use process, the decomposition efficiency of tunnel pollutants is improved, thereby improving the purification efficiency of the entire nano fireproof tunnel coating.

[0035] In addition, the present invention also discloses a nano fireproof tunnel coating with a purification function, which comprises, by weight, 200-240 parts of the cerium-doped titanium dioxide-carbon fiber composite material, 100-140 parts of bactericidal and insect-repellent composite powder, 200-250 parts of inorganic alkali metal silicate, 150-250 parts of modified silica sol, 100-150 parts of kaolin, 60-100 parts of expanded vermiculite, 10-20 parts of vitrified microspheres, 20-50 parts of glass microspheres, 80-120 parts of aluminum hydroxide, 10-20 parts of ammonium polyphosphate APP, 12-15 parts of melamine, 100-200 parts of nitrogen-vanadium co-doped nano titanium dioxide, 50-80 parts of organic silicon modifier, 70-90 parts of composite auxiliary agent and 150-180 parts of flame retardant.

[0036] The bactericidal and anthelmintic composite powder comprises 10-15 parts of patchouli, 2-6 parts of zedoaria, 5-10 parts of wild chrysanthemum, 4-6 parts of santalin, 6-9 parts of atractylodes, 6-9 parts of wormwood, 2-4 parts of mint, 8-10 parts of forsythia, 1-3 parts of schizonepeta, and 5-8 parts of houttuynia cordata.

[0037] The flame retardant is a mixture of resorcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), tributyltin oxide, molybdenum hydroxide, activated clay and aluminum hydroxide in a mass ratio of 1:2:1:1:1:3; and the particle size of kaolin is controlled to be 1-5 μm.

[0038] The preparation method of the above-mentioned nano fireproof tunnel coating with purification function is: S1: Weigh 200-240 parts of cerium-doped titanium dioxide-carbon fiber composite material, 100-140 parts of bactericidal and insect repellent composite powder, 200-250 parts of inorganic alkali metal silicate, 150-250 parts of modified silica sol, 100-150 parts of kaolin, 60-100 parts of expanded vermiculite, 10-20 parts of vitrified microspheres, 20-50 parts of glass microspheres, 80-120 parts of aluminum hydroxide, 10-20 parts of ammonium polyphosphate APP, 12-15 parts of melamine, 100-200 parts of nitrogen-vanadium co-doped nano titanium dioxide, 50-80 parts of organosilicon modifier, 70-90 parts of composite auxiliary agent and 150-180 parts of flame retardant; and beat and crush the expanded vermiculite, kaolin and aluminum hydroxide, and store the crushed materials separately; S2: After uniformly mixing the inorganic alkali metal silicate, modified silica sol and crushed kaolin, add cerium-doped titanium dioxide-carbon fiber composite material, crushed expanded vermiculite, vitrified microspheres and glass microspheres; add water and stir, let stand for 10 minutes after sufficient stirring, and then continue to stir for 20 minutes, and then let stand for another 10 minutes after the stirring is completed; then add flame retardant, ammonium polyphosphate APP, melamine, and continue to stir, after stirring evenly, add the remaining materials, and continue to stir evenly to obtain the nano fireproof tunnel coating with purification function.

[0039] In the present invention, nano-purification materials are used on the inner walls and road surfaces of the tunnel. The materials have fire resistance and can even be used together with asphalt, fire-retardant coatings, etc. The nano-purification materials can catalyze pollutants in the air and decompose volatile organic matter into CO2 and H2O, thereby making the interior of the highway tunnel safer and more environmentally friendly, and improving the overall safety and greenness during use.

[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0041] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercially available products, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0042] Example 1 A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material comprises the following steps: S1: pretreating the activated carbon fiber, specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 3 mm; grinding the cut activated carbon fiber to a particle size of 200 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 30 minutes respectively, washing, and drying at 120°C, thereby completing the pretreatment process of the activated carbon fiber.

[0043] S2: The activated carbon fiber was immersed in titanium dioxide sol at a mass ratio of 1:2, and ultrasonically treated at a frequency of 50 kHz and a temperature of 60°C for 70 min. After drying, it was calcined at 400°C in a nitrogen atmosphere for 3 h to obtain activated carbon fiber loaded with titanium dioxide; The titanium dioxide sol is prepared by 18 parts of low carbon alcohol, 20 parts of titanium-containing compound, 1.5 parts of inhibitor, and 4 parts of aqueous solution with a pH of 6.5, in parts by mass; The low-carbon alcohol is methanol, the titanium-containing compound is sodium metatitanate, the inhibitor is maleic anhydride, and glucose is added as a pore-forming agent during the preparation; S3: The activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution at a mass ratio of 1:0.5, ultrasonically treated at a temperature of 50°C for 20 minutes, dried, and calcined at a temperature of 200°C in a nitrogen atmosphere for 3 hours to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0044] In addition, the present embodiment also discloses a nano fireproof tunnel coating with a purification function, which includes, by weight, 200 parts of the cerium-doped titanium dioxide-carbon fiber composite material prepared in the present embodiment, 100 parts of a bactericidal and insect repellent composite powder, 200 parts of an inorganic alkali metal silicate, 250 parts of a modified silica sol, 150 parts of kaolin, 100 parts of expanded vermiculite, 10 parts of vitrified microspheres, 50 parts of glass microspheres, 120 parts of aluminum hydroxide, 20 parts of ammonium polyphosphate APP, 15 parts of melamine, 100 parts of nitrogen-vanadium co-doped nano titanium dioxide, 50 parts of an organosilicon modifier, 70 parts of a composite auxiliary agent, and 150 parts of a flame retardant.

[0045] Figure 2 This is a SEM image of a cerium-doped titanium dioxide-carbon fiber composite material prepared in an embodiment of the present invention. It can be seen from the figure that the staggered wrinkles and mesh structure on the surface of the composite material can effectively provide more active sites and promote photocatalytic reactions. The doping of cerium helps to reduce the recombination of electron-hole pairs and increase the transmission rate of photogenerated electrons, which is crucial to the photocatalytic process. In addition, the wrinkles and porous structure help the material maintain stability under high temperature conditions. The multi-level, interwoven structure of the material provides mechanical toughness and stability, which can effectively disperse external stress and prevent the material from deforming or breaking in a hot environment. At the same time, the addition of carbon fiber not only improves the conductivity of the material, but also enhances its high temperature resistance. In general, the surface structural characteristics and composition of the composite material enable it to maintain good stability at high temperatures, have excellent photocatalytic activity, and can efficiently degrade volatile organic compounds.

[0046] Comparative Example 1 This comparative example provides a nano fireproof tunnel coating with a purification function, which differs from the fireproof coating prepared in Example 1 in that the cerium-doped titanium dioxide-carbon fiber composite material is replaced with a pure titanium dioxide powder material.

[0047] Comparative Example 2 This comparative example provides a nano fireproof tunnel coating with a purification function, which is different from the fireproof coating prepared in Example 1 in that no cerium-doped titanium dioxide-carbon fiber composite material is added.

[0048] Figure 3 The VOC degradation performance test comparison results of the nano fire-retardant tunnel coating with purification function prepared in Example 1 of the present invention and the coatings prepared in Comparative Example 1 and Comparative Example 2 are shown in the figure. The figure shows the changes in the degradation efficiency of the three fire-retardant coatings for volatile organic compounds at different temperatures. As can be seen from the figure, for the fire-retardant coating prepared in Example 1, in the temperature range from 100°C to 600°C, the material always shows a relatively stable and significant VOC degradation ability, and the VOC degradation efficiency remains at a high level (74%~85%), especially at high temperatures (500°C~600°C), its degradation efficiency is still maintained at about 75%, which is significantly better than Comparative Example 1 and Comparative Example 2. The VOC degradation efficiency of the fire-retardant coating in Comparative Example 1 decreases significantly with the increase of temperature, while the fire-retardant coating in Comparative Example 2 does not have catalytic degradation ability. The results show that the cerium-doped titanium dioxide-carbon fiber composite material can maintain excellent catalytic activity and stability at high temperatures.

[0049] Example 2 A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material comprises the following steps: S1: pretreating the activated carbon fiber, specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 2 mm; grinding the cut activated carbon fiber to a particle size of 200 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 25 minutes respectively, washing, and drying at 110°C, thereby completing the pretreatment process of the activated carbon fiber.

[0050] S2: The activated carbon fiber was immersed in titanium dioxide sol at a mass ratio of 1:2, and ultrasonically treated at a frequency of 40 kHz and a temperature of 55°C for 80 min. After drying, it was calcined at 300°C in a helium atmosphere for 2 h to obtain activated carbon fiber loaded with titanium dioxide; The titanium dioxide sol is prepared by 18 parts of low-carbon alcohol, 18 parts of titanium-containing compound, 1.5 parts of inhibitor, and 3 parts of aqueous solution with a pH of 6.5, in parts by mass; The low-carbon alcohol is ethanol, the titanium-containing compound is titanium dioxide, the inhibitor is maleic anhydride, and a pore-forming agent is added during the preparation of the titanium dioxide sol; the pore-forming agent is starch.

[0051] S3: The activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution at a mass ratio of 1:0.5, ultrasonically treated at a temperature of 20°C for 20 minutes, dried, and calcined at a temperature of 200°C in a nitrogen atmosphere for 4 hours to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0052] In addition, the present invention also discloses a nano fireproof tunnel coating with a purification function, which comprises, by weight, 200 parts of the above-mentioned cerium-doped titanium dioxide-carbon fiber composite material, 100 parts of bactericidal and insect-repellent composite powder, 200 parts of inorganic alkali metal silicate, 150 parts of modified silica sol, 100 parts of kaolin, 60 parts of expanded vermiculite, 10 parts of vitrified microspheres, 20 parts of glass microspheres, 80 parts of aluminum hydroxide, 10 parts of ammonium polyphosphate APP, 12 parts of melamine, 100 parts of nitrogen-vanadium co-doped nano titanium dioxide, 50 parts of organic silicon modifier, 70 parts of composite auxiliary agent and 150 parts of flame retardant.

[0053] Example 3 A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material comprises the following steps: S1: pretreating the activated carbon fiber, specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 5 mm; grinding the cut activated carbon fiber to a particle size of 300 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 35 minutes respectively, washing, and drying at 130°C, thereby completing the pretreatment process of the activated carbon fiber.

[0054] S2: The activated carbon fiber was immersed in titanium dioxide sol at a mass ratio of 1:3, and ultrasonically treated at a frequency of 55 kHz and a temperature of 65°C for 80 min. After drying, it was calcined at 500°C in a nitrogen atmosphere for 2 h to obtain activated carbon fiber loaded with titanium dioxide; The titanium dioxide sol is prepared by mixing 21 parts of low-carbon alcohol, 20 parts of titanium-containing compound, 2.5 parts of inhibitor, and 5 parts of aqueous solution with a pH of 7.5, in parts by mass; The low-carbon alcohol is propanol, the titanium-containing compound is titanium tetrachloride, the inhibitor is azelaic acid monoester, and a pore-forming agent is added during the preparation of the titanium dioxide sol; the pore-forming agent is hexadecyltrimethylammonium bromide.

[0055] S3: The activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution at a mass ratio of 1:2, ultrasonically treated at a temperature of 50°C for 60 minutes, dried, and calcined at a temperature of 220°C in a nitrogen atmosphere for 4 hours to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0056] In addition, the present invention also discloses a nano fireproof tunnel coating with a purification function, which comprises, by weight, 240 parts of the above-mentioned cerium-doped titanium dioxide-carbon fiber composite material, 140 parts of bactericidal and insect-repellent composite powder, 250 parts of inorganic alkali metal silicate, 250 parts of modified silica sol, 150 parts of kaolin, 100 parts of expanded vermiculite, 20 parts of vitrified microspheres, 50 parts of glass microspheres, 120 parts of aluminum hydroxide, 20 parts of ammonium polyphosphate APP, 15 parts of melamine, 200 parts of nitrogen-vanadium co-doped nano titanium dioxide, 80 parts of organic silicon modifier, 90 parts of composite auxiliary agent and 180 parts of flame retardant.

[0057] Example 4 A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material comprises the following steps: S1: pretreating the activated carbon fiber, specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 3 mm; grinding the cut activated carbon fiber to a particle size of 250 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 30 minutes respectively, washing, and drying at 120°C, thereby completing the pretreatment process of the activated carbon fiber.

[0058] S2: The activated carbon fiber was immersed in titanium dioxide sol at a mass ratio of 1:2.5, and ultrasonically treated at a frequency of 50 kHz and a temperature of 60°C for 75 min. After drying, it was calcined at 400°C in a nitrogen atmosphere for 3 h to obtain activated carbon fiber loaded with titanium dioxide; The titanium dioxide sol is prepared by 20 parts of low carbon alcohol, 20 parts of titanium-containing compound, 2 parts of inhibitor, and 4 parts of water with a pH value of 7 according to the weight percentage; The low-carbon alcohol is butanol, the titanium-containing compound is titanium tetrachloride, the inhibitor is azelaic acid monoester, and a pore-forming agent is added during the preparation of the titanium dioxide sol. The pore-forming agent is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0059] S3: The activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution at a mass ratio of 1:1, ultrasonically treated at a temperature of 30°C for 40 minutes, dried, and calcined at a temperature of 210°C in a nitrogen atmosphere for 3 hours to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0060] In addition, the present invention also discloses a nano fireproof tunnel coating with a purification function, which comprises, by weight, 220 parts of the above-mentioned cerium-doped titanium dioxide-carbon fiber composite material, 120 parts of bactericidal and insect repellent composite powder, 230 parts of inorganic alkali metal silicate, 200 parts of modified silica sol, 130 parts of kaolin, 80 parts of expanded vermiculite, 15 parts of vitrified microspheres, 30 parts of glass microspheres, 100 parts of aluminum hydroxide, 15 parts of ammonium polyphosphate APP, 13 parts of melamine, 150 parts of nitrogen-vanadium co-doped nano titanium dioxide, 60 parts of organic silicon modifier, 80 parts of composite auxiliary agent and 160 parts of flame retardant.

[0061] Example 5 A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material comprises the following steps: S1: pretreating the activated carbon fiber, specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 5 mm; grinding the cut activated carbon fiber to a particle size of 260 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 35 minutes respectively, washing, and drying at 110°C, thereby completing the pretreatment process of the activated carbon fiber.

[0062] S2: The activated carbon fiber was immersed in titanium dioxide sol at a mass ratio of 1:3, and ultrasonically treated at a frequency of 50 kHz and a temperature of 59°C for 80 min. After drying, it was calcined at 400°C in a nitrogen atmosphere for 2 h to obtain activated carbon fiber loaded with titanium dioxide; The titanium dioxide sol is prepared by mixing 19 parts of low-carbon alcohol, 20 parts of titanium-containing compound, 2 parts of inhibitor, and 5 parts of aqueous solution with a pH of 6.5 to 7.5. The low-carbon alcohol is propanol, the titanium-containing compound is titanium dioxide, the inhibitor is maleic anhydride; and the pore-forming agent is hexadecyltrimethylammonium bromide.

[0063] S3: The activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution at a mass ratio of 1:2, ultrasonically treated at a temperature of 50°C for 40 minutes, dried, and calcined at a temperature of 210°C in a nitrogen atmosphere for 4 hours to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0064] In addition, the present invention also discloses a nano fireproof tunnel coating with a purification function, which comprises, by weight, 200 parts of the above-mentioned cerium-doped titanium dioxide-carbon fiber composite material, 110 parts of bactericidal and insect repellent composite powder, 240 parts of inorganic alkali metal silicate, 240 parts of modified silica sol, 120 parts of kaolin, 80 parts of expanded vermiculite, 18 parts of vitrified microspheres, 24 parts of glass microspheres, 110 parts of aluminum hydroxide, 15 parts of ammonium polyphosphate APP, 13 parts of melamine, 160 parts of nitrogen-vanadium co-doped nano titanium dioxide, 70 parts of organic silicon modifier, 90 parts of composite auxiliary agent and 170 parts of flame retardant.

[0065] Example 6 A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material comprises the following steps: S1: pretreating the activated carbon fiber, specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 5 mm; grinding the cut activated carbon fiber to a particle size of 260 mesh; soaking the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution for 35 minutes respectively, washing, and drying at 110°C, thereby completing the pretreatment process of the activated carbon fiber.

[0066] S2: The activated carbon fiber was immersed in titanium dioxide sol at a mass ratio of 1:3, and ultrasonically treated at a frequency of 50 kHz and a temperature of 59°C for 80 min. After drying, it was calcined at 400°C in a nitrogen atmosphere for 2 h to obtain activated carbon fiber loaded with titanium dioxide; The titanium dioxide sol is prepared by mixing 19 parts of low-carbon alcohol, 20 parts of titanium-containing compound, 2 parts of inhibitor, and 5 parts of aqueous solution with a pH of 6.5 to 7.5. The low-carbon alcohol is propanol, the titanium-containing compound is titanium dioxide, the inhibitor is dibutyl phthalate; and the pore-forming agent is cellulose.

[0067] S3: The activated carbon fiber loaded with titanium dioxide is immersed in a cerium nitrate solution at a mass ratio of 1:2, ultrasonically treated at a temperature of 50°C for 40 minutes, dried, and calcined at a temperature of 210°C in a nitrogen atmosphere for 4 hours to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

[0068] In addition, the present invention also discloses a nano fireproof tunnel coating with a purification function, which comprises, by weight, 200 parts of the above-mentioned cerium-doped titanium dioxide-carbon fiber composite material, 110 parts of bactericidal and insect repellent composite powder, 240 parts of inorganic alkali metal silicate, 240 parts of modified silica sol, 120 parts of kaolin, 80 parts of expanded vermiculite, 18 parts of vitrified microspheres, 24 parts of glass microspheres, 110 parts of aluminum hydroxide, 15 parts of ammonium polyphosphate APP, 13 parts of melamine, 160 parts of nitrogen-vanadium co-doped nano titanium dioxide, 70 parts of organic silicon modifier, 90 parts of composite auxiliary agent and 170 parts of flame retardant.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a cerium-doped titanium dioxide-carbon fiber composite material, characterized in that: The following steps are involved: S1: immersing activated carbon fiber in titanium dioxide sol, ultrasonically treating, drying and then calcining to obtain activated carbon fiber loaded with titanium dioxide; S2: immersing the activated carbon fiber loaded with titanium dioxide in a cerium nitrate solution, ultrasonically treating it, drying it, and then calcining it to obtain the cerium-doped titanium dioxide-carbon fiber composite material.

2. The method for preparing a cerium-doped titanium dioxide-carbon fiber composite material according to claim 1, characterized in that: The titanium dioxide sol is prepared by 18 to 21 parts of low carbon alcohol, 18 to 20 parts of titanium-containing compound, 1.5 to 2.5 parts of inhibitor, and 3 to 5 parts of aqueous solution with a pH of 6.5 to 7.5, in parts by mass; The low-carbon alcohol is at least one of methanol, ethanol, propanol and butanol; The titanium-containing compound is at least one of titanium dioxide, sodium metatitanate and titanium tetrachloride; The inhibitor is at least one of maleic anhydride, dibutyl phthalate and azelaic acid monoester.

3. The method for preparing a cerium-doped titanium dioxide-carbon fiber composite material according to claim 1, characterized in that: A pore-forming agent is also added during the preparation of the titanium dioxide sol; the pore-forming agent is at least one of glucose, starch, cellulose, hexadecyltrimethylammonium bromide and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

4. The method for preparing a cerium-doped titanium dioxide-carbon fiber composite material according to claim 1, characterized in that: In step S1, the activated carbon fiber is pretreated before being immersed in the titanium dioxide sol; the pretreatment is specifically: cutting the activated carbon fiber so that the cross-sectional diameter of the activated carbon fiber after cutting is 2~5mm; grinding the cut activated carbon fiber to a particle size of 200~300 mesh; placing the ground product in anhydrous ethanol, sodium hydroxide solution, and dilute nitric acid solution in turn for 25~35min, and after washing, drying at 110~130°C to complete the pretreatment process of the activated carbon fiber.

5. The method for preparing a cerium-doped titanium dioxide-carbon fiber composite material according to claim 1, characterized in that: In step S1, the mass ratio of the activated carbon fiber to the titanium dioxide sol is 1:(2-3); the frequency of ultrasonic treatment is 40-55 kHz, the time is 70-80 min, and the temperature is 55-65°C.

6. The method for preparing a cerium-doped titanium dioxide-carbon fiber composite material according to claim 1, characterized in that: In step S1, during the calcination process, the temperature is 300-500°C, the time is 2-4 hours, and the calcination atmosphere is nitrogen or helium.

7. The method for preparing a cerium-doped titanium dioxide-carbon fiber composite material according to claim 1, characterized in that: In step S2, the mass ratio of the activated carbon fiber loaded with titanium dioxide to cerium nitrate is 1:(0.5-2); the ultrasonic treatment time is 20-60 minutes, and the temperature is 20-50°C.

8. The method for preparing a cerium-doped titanium dioxide-carbon fiber composite material according to claim 1, characterized in that: During the calcination process of step S2, the temperature is 200-220°C, the time is 2-4 hours, and the calcination atmosphere is nitrogen or helium.

9. A cerium-doped titanium dioxide-carbon fiber composite material, characterized in that: The cerium-doped titanium dioxide-carbon fiber composite material is prepared by the method described in any one of claims 1 to 8; the degradation rate of VOCs of the cerium-doped titanium dioxide-carbon fiber composite material is 74% to 85% under ultraviolet light irradiation within 100 to 600°C.

10. A nano fireproof tunnel coating with purification function, characterized in that: According to the weight parts, it includes 200-240 parts of the cerium-doped titanium dioxide-carbon fiber composite material described in claim 9, 100-140 parts of bactericidal and insect repellent composite powder, 200-250 parts of inorganic alkali metal silicate, 150-250 parts of modified silica sol, 100-150 parts of kaolin, 60-100 parts of expanded vermiculite, 10-20 parts of vitrified microspheres, 20-50 parts of glass microspheres, 80-120 parts of aluminum hydroxide, 10-20 parts of ammonium polyphosphate, 12-15 parts of melamine, 100-200 parts of nitrogen-vanadium co-doped nano titanium dioxide, 50-80 parts of organic silicon modifier, 70-90 parts of composite auxiliary agent and 150-180 parts of flame retardant.

Citation Information

Patent Citations

  • Method for improving efficiency of visible light response doping-type M-TiO2 / AC photocatalyst

    CN101905154A

  • Cerium-doped nano titanium dioxide / activated carbon fiber composite photocatalyst for air purification and preparation method thereof

    CN102658115A

  • Improved charcoal-based phosphorous removal adsorbent and preparation method thereof

    CN103877937A

  • Activated carbon fiber loading titanium dioxide composite photocatalytic material and preparation method and application thereof

    CN104888750A

  • Super self-cleaning inorganic fireproof tunnel coating and preparation method thereof

    CN113265166A

Cited By

  • Silicon-titanium composite antifogging coating as well as preparation method and application thereof

    CN120137436A